Assessment Of Surface Irrigation Potential And Optimization Of Cropping Pattern: Case Study Of Danse Watershed, Oromia Region - Bayush, Moges (ASTU, 2020)
Irrigation is an important investment for improving rural income through increased agricultural production. The development of irrigation holds significant potential to enhance productivity. Planning and decision making is required for Irrigation development projects based on the assessment of irrigable land together with available water resources. This study was initiated with the objective of estimating available surface water, assessing land suitability and optimization of cropping pattern in Danse watershed. The availability of water was determined from surface runoff using curve number method. As a result, the weighted curve number of the watershed was estimated as 84. Using the mean annual precipitation of Ejere station from 1987-2016, the annual volume of surface runoff generated in the watershed was 18.64 Mm3. However, all runoff volume generated in the watershed was not used for irrigation and 1/3 of runoff from rainfall suggested for other losses, the rest runoff volume 6,213,333 m3 can be used by the farmers for crop production. Land suitability for surface irrigation was identified by considering the irrigation suitability factors such as soil, slope and land use/land cover through implementing Arc-GIS 10.4. Soil suitability was examined in terms of soil depth, texture and drainage. The suitability of each parameter analyze individually based on FAO criteria for surface irrigation development and then the weighted overlay analysis was provided to get the overall suitability. The result of the weighted overlay analysis revealed that out of the total 2170 ha of land 85.36 ha were highly suitable, 1475.68 ha moderately suitable, 596.67 ha marginally suitable and 4.78 ha of the area were unsuitable for surface irrigation development. To grow crops on these identified irrigable areas, four dominant crops were selected and their irrigation water requirement was calculated by using CropWat 8.0 model. Optimization of cropping pattern was performed with the available land and water resource to maximize the net benefit from crop production using Lingo software. Result signifies that from the dominant crops area allocation of 164 ha onion, 8 ha Tomato, 5 ha Cabbage and 15 ha wheat the maximum production benefit was 57,748,130 Birr. Hence, in order to get the optimum benefit out of the land, proper utilization of its resources is inevitable. Therefore, this study would help farmers, decision makers, investors and planners in better identification of profitable irrigation investment opportunities in the watershed and the outputs bring relief for other researchers as an input.
Keywords: Cropping pattern, Curve number, Land suitability, Linear programming, Lingo, Optimization, Runoff, Water availability